Loss of PDK1 Induces Meiotic Defects in Oocytes From Diabetic Mice - Ge, Juan; Zhang, Na; Tang, Shoubin; Hu, Feifei; Hou, Xiaojing; Sun, Hongzheng; Han, Longsen; Wang, Qiang (Frontiers in Cell and Developmental Biology, 2021)
Maternal diabetes has been shown to impair oocyte quality; however, the underlying mechanisms remain unclear. Here, using a streptozotocin (STZ)-induced diabetic mouse model, we first detected and reduced expression of pyruvate dehydrogenase kinase 1 (PDK1) in diabetic oocytes, accompanying with the lowered phosphorylation of serine residue 232 on α subunit of the pyruvate dehydrogenase (PDH) complex (Ser232-PDHE1α). Importantly, forced expression of PDK1 not only elevated the phosphorylation level of Ser232-PDHE1α, but also partly prevented the spindle disorganization and chromosome misalignment in oocytes from diabetic mice, with no beneficial effects on metabolic dysfunction. Moreover, a phospho-mimetic S232D-PDHE1α mutant is also capable of ameliorating the maternal diabetes-associated meiotic defects. In sum, our data indicate that PDK1-controlled Ser232-PDHE1α phosphorylation pathway mediates the effects of diabetic environment on oocyte competence.